Fatty Acid Allosteric Regulation of C-H Activation in Plant and Animal Lipoxygenases - Adam R. Offenbacher; Theodore R. Holman (Molecules, 2020)
Lipoxygenases (LOXs) catalyze the (per) oxidation of fatty acids that serve as important mediators for cell signaling and inflammation. These reactions are initiated by a C-H activation step that is allosterically regulated in plant and animal enzymes. LOXs from higher eukaryotes are equipped with an N-terminal PLAT (Polycystin-1, Lipoxygenase, Alpha-Toxin) domain that has been implicated to bind to small molecule allosteric effectors, which in turn modulate substrate specificity and the rate-limiting steps of catalysis. Herein, the kinetic and structural evidence that describes the allosteric regulation of plant and animal lipoxygenase chemistry by fatty acids and their derivatives are summarized.